Integrated Pest Management: Success Stories and Key Takeaways - Das, Nikita; G S, Sujatha; Teja, Katta Subramanya Sai; Hazarika, Sanjay; E, Vidya Madhuri; J S, Rupali; Devi, Leishangthem Sarnabati; Bala, Biplove (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Integrated Pest Management (IPM) has revolutionized pest control in various agricultural settings, including orchards. By blending cultural, biological, and chemical methods, IPM aims to minimize pest damage while reducing environmental and health impacts. One of the most successful strategies within IPM is mating disruption, which uses synthetic pheromones to confuse male insects and prevent them from finding mates. This technique has been particularly effective against pests like the codling moth in apple and pear orchards, significantly reducing insecticide use by up to 90% in some regions.The implementation of IPM in orchards has numerous long-term advantages. Lower manufacturing costs, less environmental contamination, and increased worker safety have all resulted from reduced pesticide use. Furthermore, a healthier ecological balance has been promoted by the rise in natural predators and parasitoids brought about by the decrease in chemical treatments. Many growers have reported greater fruit quality due to more targeted pest control and healthier trees, despite worries that reduced use of pesticides would harm fruit quality. Important pests have also been suppressed regionally as a result of IPM's efficacy, such as the codling moth in the Pacific Northwest, whose populations have dropped to the point where little intervention is needed. Economic assessments highlight IPM's financial sustainability by demonstrating considerable long-term cost savings. According to one study, IPM adopters in apple orchards in Nova Scotia had 25% reduced pest management expenses over a ten-year period than those using conventional approaches. These results demonstrate how integrated pest management (IPM) has the ability to provide long-term, efficient pest control that is advantageous to growers, the environment, and consumers alike. IPM's widespread use attests to its effectiveness and sustainability. Integrative pest management (IPM) ensures the long-term health and production of agricultural systems by combining various pest control techniques into a balanced solution that satisfies both ecological and financial requirements.